Exit from Discord and models of its applications in the personal - Al-Qawasmi, Abdul-Sameeh Fawzi Abdul-Sameeh (Journal of Islamic Sciences, 2021)
Our first scientists have been an example of a role model in removing the dispute in the issues of jurisprudence, they worked on the root of many issues came the rule "exit from the dispute is desirable" with its conditions and controls when imams were a great building stone in jurisprudence in various fields, and the main goal of this research indicate the possibility of exit from the dispute; how, sections, conditions and scope, represented by five issues In the personal status as a model to get out of the dispute, these issues are the desirability of the permission of the adult virgin parent when marrying her; and the testimony of the return in the retroactive divorce, the testimony of the marriage contract, and marriage with the intention of divorce or analysis, and the requirement of the Guardian in the marriage contract, in them, attributing the verses and Hadiths to its muzanha, the researcher has come to the conclusion that the exit of The implementation of the exit from the dispute in matters of personal status reduces the gap in the dispute, which elevates this law and relieves people, making it work in line with the current era without prejudice to the origins of the Shariah provisions.
Keywords: jurisprudence; disagreement; marriage; divorce; exit from disagreement; personal status